Analysis of behaviour in the emissions of carbon dioxide of Brazil and other countries based on the Kaya Identity and the Emission Profile - Gustavo dos Reis Feijó; João Jose de Assis Rangel (Desenvolvimento e Meio Ambiente, 2018)
This study analyzes the behavior of carbon dioxide emissions with regard to the economic and population growth of Brazil and other selected countries over the last two decades. We applied the Kaya Identity and the Emission Profile to model a data set related to Brazil and six other countries. The most recent data available and applied as a source of analysis during this research are from the International Energy Agency for the period 1990 to 2014. The results presented two antagonistic conclusions for Brazil. The first one is that, when comparing to the other countries under investigation, Brazil has the best position regarding the total volume of polluting gases released into the atmosphere. The second conclusion demonstrated that the carbon dioxide emissions emitted by Brazil have been growing more than the population increase. That is, if the country continues as it is, it could lose the important condition of a cleaner energy matrix.